2017
DOI: 10.1016/j.acap.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Asthma Health Disparities: Race, Hardship, Housing, and Asthma in a National Survey

Abstract: Objectives We sought to determine if racial disparities in pediatric asthma are explained by material hardship and home ownership. Methods We performed a secondary analysis of the 2011 American Housing Survey. 33,201 households with children age 6-17 years were surveyed regarding childhood asthma diagnosis and ED visits for asthma (for the youngest child with asthma in the household). Material hardship included poor housing quality, housing crowding, lack of amenities, and no vehicle access. We used logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(78 citation statements)
references
References 29 publications
2
76
0
Order By: Relevance
“…Although housing stress was explored as a cofactor for asthma in this study, poor housing in general may be a risk factor for asthma morbidity. Supporting this idea are observations by Hughes et al, 55 who examined housing quality and home ownership as independent factors in asthma morbidity in a secondary analysis of data from the 2011 American Housing Survey of 33,201 households with children age 6 to 17 years. They reported that poor housing quality increased risk for asthma diagnosis (OR ¼ 1.45), ED visits for asthma (ED ¼ 1.59), and home ownership decreased risk for asthma-related ED visits (OR ¼ 0.62).…”
Section: Stress Exposuresmentioning
confidence: 92%
“…Although housing stress was explored as a cofactor for asthma in this study, poor housing in general may be a risk factor for asthma morbidity. Supporting this idea are observations by Hughes et al, 55 who examined housing quality and home ownership as independent factors in asthma morbidity in a secondary analysis of data from the 2011 American Housing Survey of 33,201 households with children age 6 to 17 years. They reported that poor housing quality increased risk for asthma diagnosis (OR ¼ 1.45), ED visits for asthma (ED ¼ 1.59), and home ownership decreased risk for asthma-related ED visits (OR ¼ 0.62).…”
Section: Stress Exposuresmentioning
confidence: 92%
“…In fact, home rodent infestation was one of the most commonly reported negative life events, comparable to rates observed in a sample of urban Puerto Rican families of children with asthma [43]. Addressing poor housing stock is particularly critical since, beyond its relationship with elevated caregiver life stress, environmental exposures stemming from sub-standard housing were associated with higher rates of ED visits in children with asthma aged 6-17 years [44]. Recommendations to improve the quality of housing stock include implementing healthy housing guidelines for new construction, increased enforcement of housing codes, and home visiting education and environmental intervention programs to reduce trigger exposures [45].…”
Section: Discussionmentioning
confidence: 68%
“…Material hardship and home ownership were recently examined as a contributor to disparities by Hughes et al [25••]. They analyzed the 2011 American Housing Survey and found that poor housing quality was associated with asthma diagnosis and emergency department visits.…”
Section: Mechanisms Of Worse Outcomes In Disadvantaged Communitiesmentioning
confidence: 99%